Analysis of Food Security from the Perspective of National Economic Development in Indonesia - Tisa Fauzia; Yuni Agustin; Hudallah Hudallah (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2026)
Food security has become a crucial issue in global economic development, including in Indonesia, where it is closely linked to the productivity of the agricultural sector. This sector plays a strategic role not only as a food provider but also as a source of employment, a contributor to national income, and a means of income distribution. Data indicate that the agricultural sector still absorbs around 29% of the national workforce despite a structural shift toward the industrial and service sectors. The high consumption of staple foods such as rice and eggs highlights the strong dependence of society on agricultural outputs, making national economic stability closely tied to this sector. However, the agricultural sector faces several challenges, including land conversion, low productivity, and dependence on food imports. Therefore, strategic policies are required to enhance productivity, promote technological innovation, and improve farmers’ welfare in order to strengthen national food security.